The optimal dietary crude protein level improves goat production performance by enhancing the body’s antioxidant function and energy metabolism - Wang, Chunhui; Zhang, Caixia; Shah, Ali Mujtaba; Wang, Zhisheng; Qiu, Shixiu; Xu, Zhenying; Xue, Bai; Wang, Lizhi; Hu, Rui; Zou, Huawei; Jiang, Yahui; Xiao, Jianxin; et al. (Frontiers in Microbiology, 2026)
The current research was conducted to evaluate the impact of various crude protein (CP) concentrations in diets on growth performance, nutrient digestibility, nitrogen deposition, rumen fermentation, microbial community, and serum metabolomics in growing goats. Fifty healthy 4-month-old Chuannan black goats (Capra hircus) with similar body weight (13.75 ± 0.27 kg) were randomly distributed into 5 groups. Goats were fed diets with five different levels of CP: 8.12% (T8), 10.15% (T10), 12.17% (T12), 14.13% (T14), and 16.18% (T16), respectively. The total duration of the trial was 70 d, including a 14-day adaptation period. The average daily gain and feed conversion ratio displayed a quadratic upsurge and reduce respectively, with the rise of CP content in the diet. The group T14 exhibited the highest average daily gain and demonstrated the best feed conversion efficiency. A linearly (p < 0.05) increase of the digestibility of dry matter, neutral detergent fiber, and acid detergent fiber was observed, whereas a quadratic effect (p < 0.001) on nitrogen intake, fecal nitrogen, and urinary nitrogen was obtained with the increase of dietary CP. Moreover, dietary CP levels had a quadratic effect on the concentration of ruminal ammonia nitrogen (p = 0.021), rumen microbial protein (p = 0.042), total volatile fatty acid (p = 0.012), acetate (p = 0.040), isobutyrate (p = 0.024), and isovalerate (p < 0.001). Microbial metagenomics results showed that the relative abundance of Burkholderia and Bacillus increased (p < 0.05), while the relative abundance of Pseudomonas and Salmonella decreased (p < 0.05) when comparing group T14 to group T8. Metabolomic results showed that differently expressed metabolites were found to enrich the proline, glutathione and arginine metabolism, and citric acid cycle metabolic pathway. The concentration of serum genistein was positively correlated (p < 0.05, r = 0.665) with the abundance of Bacillus and negatively correlated (p < 0.05, r = −0.734) with the abundance of Pseudomonas. It is concluded that a dietary CP level of 14% enhances the antioxidant function and energy metabolism of the goats by altering the composition of rumen microorganisms, thereby improving production performance.